Intermediate care in caring for dementia, the point of view of general practitioners: A key informant survey across Europe - Dibao-Dina, Clarisse; Oger, Caroline; Foley, Tony; Torzsa, Péter; Lazic, Vanja; Kreitmayer Peštiae, Sanda; Adler, Limor; Kareli, Ana; Mallen, Christian; Heaster, Cindy; Dumitra, Gindrovel; Kurpas, Donata; et al. (Frontiers in Medicine, 2022)
Background: Intermediate care is often defined as healthcare occurring somewhere between traditional primary (community) and secondary (hospital) care settings. High quality intermediate care is important in dementia and may prevent caregiver burnout. However, very little is known about the point of intermediate care for persons with dementia in Europe. Research questions: How are intermediate care services used in the care for people with neurocognitive disorders across Europe? Objective: This study aims at describing the point of view of General Practitioners on intermediate care services for people with neurocognitive disorders across Europe. Methods: Key informant survey was sent to GPs via a self-developed questionnaire with space for open ended comments. Convenience sampling technique was used to address variations due to regional opportunities and regulations within the same country. Descriptive analyses of all intermediate care facilities groups by countries were performed. Qualitative analyses approach was used for the optional-free text to extract the reasons for the non-uniformity of the responses within the same country and discrepancies between the official rules, if any, and the responses from key informants. Results: The questionnaire was sent to 17 European countries. 583 questionnaires were analysed. The responding physicians were 48 (+/- 11) years old on average and they had been in practice for an average of 18 (+/11) years. The types of intermediate care considered were integrated at-home services, respite and relief services, day care centres and nursing homes. Their availability was considered very inhomogeneous by the majority of respondents. The main benefits cited were better medical care for the patient (78%), better quality of life for the caregiver (67%), prevention of the caregiver burden (73%) and a break for the caregiver (59%). The reported difficulties were: accessing these facilities due to limited financial support (76%) and cumbersome administrative procedures (67%). Conclusion: Intermediate care in Europe is diverse and heterogeneous. Major concerns of GPs are about the cost issues, the accessibility and the awareness of the existence of these facilities and the procedure to access them.